Controlled electrochemical growth of ultra-long gold nanoribbons - Basnet, Gobind; Panta, Krishna R.; Thapa, P. S.; Flanders, Bret N. (My University, 2017)
This paper describes the electrochemical growth of branchless gold nanoribbons with similar to 40 nm x similar to 300 nm cross sections and >100 mu m lengths (giving length-to-thickness aspect ratios of > 10(3)). These structures are useful for opto-electronic studies and as nanoscale electrodes. The 0.75-1.0V voltage amplitude range is optimal for branchless ribbon growth. Reduced amplitudes induce no growth, possibly due to reversible redox chemistry of gold at reduced amplitudes, whereas elevated amplitudes, or excess electrical noise, induce significant side-branching. The inter-relatedness of voltage-amplitude, noise, and side-branching in electrochemical nanoribbon growth is demonstrated. Published by AIP Publishing.
Citation: Basnet, G., Panta, K. R., Thapa, P. S., & Flanders, B. N. (2017). Controlled electrochemical growth of ultra-long gold nanoribbons. Applied Physics Letters, 110(7), 5. doi:10.1063/1.4976027
Keywords: Morphological Stability; Nanowires; Noise; Physics